Analisis Simultanitas Kebijakan Hutang dan Kebijakan Maturitas Hutang serta Faktor-Faktor yang Mempengaruhinya - Sunarsih Sunarsih (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
This study is aimed to test the relationship between leverage and debt maturity policies, and to reveal the factors influencing on simultaneity analysis of leverage and debt maturity policies on Indonesia manufacture industry. This specific study took 130 firms, which were listed in Jakarta Stock Exchange from 1994 until 1998, as its sample. Data are gathered through pooling data. The endogenous variables that are used in this study are: leverage and debt maturity. While the exogenous variable are: (1) invistment opportunity set, (2) firm size, (3) signaling effect, (4) non debt–tax shiled and (5) asset maturity. Using two-stage least square (2SLS) as method analysis, the result of the analysis shows that firm size and non debt–tax shield have significant influence on leverage policy, but inconsistent with the hypothesis. While firm size, signaling effect, and asset maturity have significant ifluence on debt maturity policy. This study revealed the com¬plement relationship between leverage and debt maturity. It mean that both policies have simultaneous relation¬ship positively.Keyword: Simultaneity, leverage, debt maturity, invistment opportunity set, firm size, signaling effect, non debt–tax shiled, and asset maturity.